2016
DOI: 10.1542/peds.2015-3356
|View full text |Cite
|
Sign up to set email alerts
|

First-year Daycare and Incidence of Acute Gastroenteritis

Abstract: BACKGROUND: Daycare attendance has been associated with increased acute gastroenteritis (AGE) incidence in the first years of life. We investigated the effects of first-year daycare attendance on AGE incidence and primary care contact rate up to age 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…However, our report is in agreement with a previous study done by Oldak et al (2012) in Northeastern Poland, in which higher NoV infection was detected in children between 1 and3 years of age [49]. The higher NoV infection rate in children between 1 and 3 years of age could be attributed to commingling of children in daycares, where children at this age have minimal immunity to the virus [50].…”
Section: Discussionsupporting
confidence: 93%
“…However, our report is in agreement with a previous study done by Oldak et al (2012) in Northeastern Poland, in which higher NoV infection was detected in children between 1 and3 years of age [49]. The higher NoV infection rate in children between 1 and 3 years of age could be attributed to commingling of children in daycares, where children at this age have minimal immunity to the virus [50].…”
Section: Discussionsupporting
confidence: 93%
“…At least one study reports that after first or second year in the day care environment children's immunity turns protective against symptomatic acute gastroenteritis. 26 Nevertheless, there was no question asking if the children in the households spend their days in a day care or not, so the possibility can only be hypothesised.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since the regression model showed that having two to six years old children in the household had a positive association with infections, there is a possibility that those pathogens spread into the household with children from the day care centre or outside and were transmitted to family adults without causing symptoms in the children. At least one study reports that after first or second year in the day care environment children's immunity turns protective against symptomatic acute gastroenteritis 26 . Nevertheless, there was no question asking if the children in the households spend their days in a day care or not, so the possibility can only be hypothesised.…”
Section: Discussionmentioning
confidence: 99%
“…ADI incidence was associated with having siblings and with formal childcare attendance, both of which are recognised risk factors 12,13 . The relative peak in ADI incidence rate and the longer median episode duration in the first month of life was unexpected since ADI is believed to be uncommon in healthy newborns 14 .…”
Section: Discussionmentioning
confidence: 99%
“…ADI incidence was associated with having siblings and with formal childcare attendance, both of which are recognised risk factors. 12,13 The relative peak in ADI incidence rate and the longer median episode duration in the first month of life was unexpected since ADI is believed to be uncommon in healthy newborns. 14 Our data show that this peak was driven by the relatively higher daily number of loose stools reported in the first month of life and did not result in above-average health-care utilisation.…”
Section: Discussionmentioning
confidence: 99%